2017
DOI: 10.12659/msm.900296
|View full text |Cite
|
Sign up to set email alerts
|

miR-4417 Targets Tripartite Motif-Containing 35 (TRIM35) and Regulates Pyruvate Kinase Muscle 2 (PKM2) Phosphorylation to Promote Proliferation and Suppress Apoptosis in Hepatocellular Carcinoma Cells

Abstract: BackgroundMicroRNAs (miRNAs) are a class of small non-coding RNAs that are strongly involved in various types of carcinogenesis, including hepatocellular carcinoma (HCC). This study aimed to clarify whether miR-4417 promotes HCC growth by targeting TRIM35 and regulating PKM2 phosphorylation.Material/MethodsOnline software, including TargetScan and miRanda, was used to predict the potential target of miR-4417. Real-Time PCR (qRT-PCR) and Western blot assays were performed to detect the expression levels of mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Similar to: miRNA-29b [89], miRNA-99a [90], miRNA-133b [91], miRNA-145 [92], miRNA-148a [93], miRNA-152 [93, 94], miRNA-290 [95], miRNA-326 [96], miRNA-338-3P [97], miRNA-340 [98], miRNA-369 [99], miRNA-371 [95], miR-379 [100], miRNA-675 [101], miRNA-4417 etc. [102]. While these miRNAs are targeted to the splicing factors PTBP1, hnRNPA1, and hnRNPA2, [103] the expression of PKM mRNA is shifted from PKM1 to PKM2, and the expression of PKM2 is increased [104].…”
Section: The Splicing Of Pmk2mentioning
confidence: 99%
“…Similar to: miRNA-29b [89], miRNA-99a [90], miRNA-133b [91], miRNA-145 [92], miRNA-148a [93], miRNA-152 [93, 94], miRNA-290 [95], miRNA-326 [96], miRNA-338-3P [97], miRNA-340 [98], miRNA-369 [99], miRNA-371 [95], miR-379 [100], miRNA-675 [101], miRNA-4417 etc. [102]. While these miRNAs are targeted to the splicing factors PTBP1, hnRNPA1, and hnRNPA2, [103] the expression of PKM mRNA is shifted from PKM1 to PKM2, and the expression of PKM2 is increased [104].…”
Section: The Splicing Of Pmk2mentioning
confidence: 99%
“…In addition, a previous study revealed that OTU deubiquitinase 5 suppression via hsa-miR-4417 and hsa-miR-6782 could maintain the viability of tumor cells and suppress programmed cell death (52). Song et al (53) demonstrated that, in hepatocellular carcinoma cells, miR-4417 can promote proliferation and suppress apoptosis by targeting tripartite motif-containing 35 and regulating the phosphorylation of pyruvate kinase muscle. Furthermore, the present study identified 935 target genes using four databases.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that the thyroid hormone induces miR-214 to suppress Bim expression through negatively regulating the transcription factor Forkhead box protein O1 (FoxO1) to avoid liver cell apoptosis and ROS-induced stress [110]. In addition to miR-214, there are many miRNAs that have the potential to affect the apoptosis of liver cancer cells, such as miR-155, miR-4417, miR-199a, and miR-122 [59,77,115,116]. Among them, the expression levels of miR-199a and miR-122 are associated with thyroid hormone and oxidative stress (Table 2 and Table 3) [27].…”
Section: Effect Of Thyroid Hormone On the Role Of Oxidative Stressmentioning
confidence: 99%